Human semen profile and mobile telephony: an original research study - Jayram; Kumar, Mukesh; Srinivasa, M. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Mobile telephony is recent phenomenon; it functions based on electro-magnetic radiation (EMR). It has revolutionized the telephonic communication system. Major population of world is using mobile telephony with android mobile handsets. Mobile users are rapidly increasing every day. Researchers show that Electro- Magnetic Radiation affects the human health and causes tumour, cancer and other diseases. This has also been reported that mobile telephony affects the reproductive health too. But some researchers claimed that mobile telephony does not affect human health. Therefore, this study was planned in male human volunteers to assess the possible effects of mobile telephony on semen profile. Methods: Eighty-two human male volunteers consented for our research study. Their mobile phone placing, using hour/day was recorded and these volunteers were placed in three Groups A, B and C (exposure of mobile telephony was 3-4 hours, 5-6 hours and 7-8 hours respectively and approximately). Results: Semen analysis was done using WHO method manual in our infertility research centre, Bengaluru, India. Semen analysis of these volunteers shows that decline in sperm density, motility (quantitatively and qualitatively) and enhanced percentage of abnormal sperm. It appears to be associated with duration exposure dependant. Conclusions: In conclusion, we may say that sub-fertility in human male may be associated with the use of mobile telephony along with other factors. Further research studies are needed to ascertain the possible effects of mobile telephony on human male reproductive health.